Hubungan Antara Dukungan Sosial Teman Sebaya Dengan Penyesuaian Diri Pada Mahasiswa Rantau Asal Toraja Di Salatiga - Nari Liling; Dewita Karema Sarajar (STIE AMKOP, 2023)
Being a student who will continue his education as a student after finishing high school will be a new experience in adjusting to students because it requires adjustment in a new environment. One of the factors that support adjustment in a new environment is social support from peers. The purpose of this study was to find out the relationship between peer social support and adjustment in overseas students from Toraja in Salatiga, class of 2021 & 2022. This study used a quantitative method with a sampling technique, namely a type of non-probability sampling. The samples taken amounted to 103 students. The data collection in this study was carried out using a peer social support scale with a Cronbach Alpha value of 0.923 and a self-adjustment scale with a Cronbach Alpha value of 0.734. The results showed that there was a positive relationship between peer social support and self-adjustment among overseas students from Toraja. The Pearson correlation number is positive, which is equal to 0.243, so the direction of the relationship variable is positive or interconnected, which means that social support has a relationship with self-adjustment. The higher the peer social support, the higher the student's self-adjustment. Kata kunci: Peer social support, self-adjustment, overseas students